2022
DOI: 10.1152/jn.00509.2021
|View full text |Cite
|
Sign up to set email alerts
|

Human KCNQ5 de novo mutations underlie epilepsy and intellectual disability

Abstract: We identified six novel de novo human KCNQ5 variants in children with motor/language delay, intellectual disability (ID) and/or epilepsy by whole-exome sequencing. These variants comprised of two nonsense and four missense alterations, were functionally characterized by electrophysiology in HEK293/CHO cells, together with four previously reported KCNQ5 missense variants (Lehman, et al., 2017). Surprisingly, all eight missense variants resulted in gain-of-function (GOF) due to hyperpolarized voltage-dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 95 publications
2
10
0
Order By: Relevance
“…Moreover, this study shows that the more severe GOF variants were found in more severely affected individuals, while milder GOF variants and the truncating LOF variants belonged to individuals with a milder phenotype. 17 This is in line with a second recent publication that found two pore variants to cause a GOF in individuals with DEE. 18 The individuals presented here show a milder phenotype as compared to the three studies mentioned and two carriers were even asymptomatic (one with R359C and one with Q735R).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, this study shows that the more severe GOF variants were found in more severely affected individuals, while milder GOF variants and the truncating LOF variants belonged to individuals with a milder phenotype. 17 This is in line with a second recent publication that found two pore variants to cause a GOF in individuals with DEE. 18 The individuals presented here show a milder phenotype as compared to the three studies mentioned and two carriers were even asymptomatic (one with R359C and one with Q735R).…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, the functional severity of the GOF seems to correlate with the severity in the phenotype of the patient. 17 Similar patterns of GOF variants inducing much more severe phenotypes such as DEE and LOF variants inducing milder phenotypes such as GGE have been described for other genes such as SCN8A, 36 SCN2A 37 and KCNA2. 38 For KCNQ5 , it seems that any significant LOF can contribute to an epileptic phenotype or ID of varying severity, which might be influenced by other individually differing factors, such as compensatory effects, the genetic background or environmental determinants.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Hence, the pronounced insensitivity to Ca 2+ of P369L homomeric KCNQ1 and heteromeric Q1E2 channels could rely on a downstream mechanism circumventing the primary Ca 2+ -sensing process. The functional importance of a proline at this position for all KCNQ family members is indicated by the gain-of-function of the KCNQ5 variants P369R and P369T, affecting the proline analogous to KCNQ1 P369 [ 53 , 54 ]. Heterozygous gain- and loss-of-function variants in KCNQ5 cause pediatric neurological disorders of different severities [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The functional importance of a proline at this position for all KCNQ family members is indicated by the gain-of-function of the KCNQ5 variants P369R and P369T, affecting the proline analogous to KCNQ1 P369 [ 53 , 54 ]. Heterozygous gain- and loss-of-function variants in KCNQ5 cause pediatric neurological disorders of different severities [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%